Disorders of the central nervous system cognitive and mnestic functions in genetic arterial hypertension and with the use of beta-blockers of different generations - A. O. Svitlytskyi; A. A. Yehorov; O. V. Melnikova; T. A. Hrekova (Сучасні медичні технології)
Arterial hypertension is currently one of the most common diseases in the world. A long-term increase in pressure results in changes in the target organs, the healthy functioning of which depends on a stable blood supply (kidneys, eyes, brain), which is primarily caused by damage to small vessels. β-blockers are among the drugs with proven effectiveness in the treatment of hypertension, but their long-term use has different effects on the cognitive sphere, which is determined by the coordination of neurotrophic and neurotransmitter processes in the corresponding brain structures.